An Essentialist View of Biological Sex Remains Alive and Well: A Response to Penner, Cordero, and Nichols - Wingard, John; Madueme, Hans (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2025)
In response to a recent article by Myron Penner, April Cordero, and Amanda Nichols in this journal, this essay offers a critical analysis. Their article makes a case against gender essentialism rooted in biology, drawing from the biology of sex determination. While commending their thorough exposition of the science of sex determination, we argue that most of their anthropological conclusions are unfounded. After reviewing their article, we present several criticisms that undermine their case. In particular, we take issue with the authors’ methodological commitments and demonstrate that the evidence they present from the science of human sex determination does not convincingly support rejecting an essentialist view of biological sex. Furthermore, we argue that human sexuality solidifies into a binary and fixed state following sex determination during gestation. Contrary to the original essay, our analysis concludes that the science of sex determination leaves wide open the possibility that some biology-based form of gender essentialism is true.